ANALISIS SIKAP KONSUMEN TERHADAP MOTOR MATIK DI KOTA PALEMBANG - A NAZARUDDIN .; M EKO FITRIANTO (Program Studi Magister Manajemen FE Unsri, 2014)
This study attempts to examine how consumer attitudes toward automatic motorcycle. In conducting the study, researchers used a descriptive conclusive research in a single cross-sectional shape. Conclusive research is used to test specific hypotheses and test the connection. The sample used is the general public who were in the city of Palembang as many as 100 respondents using convenience sampling method. The analysis used in this study is the analysis of the theory of Fishbein-Ajzen attitude. In this analysis will be seen how the trend of consumer attitudes are positive or negative affect marketing mix variables automatic motorcycle. Results of the study showed consumer attitudes toward automatic motor generally neutral (7 variables) and positive in 3 variables, namely: Motor matic easy to use (3453), Motor matic comfortable ride (3384) and Motor matic cool design (3076)